IMPACT OF CREATIVE TOURISM DEVELOPMENT ON CONDITIONS SOCIO-ECONOMIC LOCAL COMMUNITIES IN DAGO POJOK TOURISM VILLAGES - Nabila, Affra Siti; Marsongko, Eka Pramita; Endah Trihayuningtyas (International Journal of Sustainable Competitiveness on Tourism, 2023)
Changes in tourism trends make tourists need to be more interactive and try to overcome the experience of not just being tourists who are served by actors in the tourism industry. The development of creative tourism is like this, and besides being able to meet the needs of tourists, the development of creative tourism can also create jobs and improve people's welfare. The city of Bandung is a city owned by the Ministry of Tourism and Creative Economy to be included in the UNESCO World Network of creative cities. However, the city of Bandung also has a limited typology of natural tourism. This is what makes the Bandung City government take advantage of the creative spaces that exist around the community, namely Kampung-Kota as an alternative for developing tourism potential. The Bandung City Government has developed 30 creative tourism villages in 30 Bandung City Districts. And Dago Pojok Creative Tourism Village is the first creative tourism village in Bandung City and the ideas from the Dago Pojok Village community become an example for other Creative Tourism Villages in Bandung City. The purpose of this study was to identify and determine the actual conditions of creative tourism in the Dago Pojok Creative Tourism Village as a creative tourist attraction and its impact on the socio-economic conditions of the community. The method used is descriptive with a qualitative approach with analysis using coding tools. The development of creative tourism in the Dago Pojok Creative Tourism Village has had a positive impact on the socio-economic life of the community. Judging from the relationship between the community, education, increased community income, and the opening of new job opportunities for the community. Even so, the overall socio-economic impact for the community has not been sustainable. Because creative tourism activities have not been able to become the main livelihood and uncertain community income which depends on the number of tourist visits to Dago Pojok Creative Village